THE EFFECT OF VOCABULARY MASTERY AND READING INTEREST TOWARDS THE ABILITY OF NARATIVE TEXT COMPREHENSION (Survey at SMP Negeri East Jakarta) - Anis Ma'rifah; Mamik Suendarti (INFERENCE: Journal of English Language Teaching, 2018)
The purpose of knowing and analyzing the influence of vocabulary mastery and reading interest on the Ability to Understand Narrative Text. The population observed in this research is the students of class VIII (Eight) SMP Negeri in Kecamatan Makasar East Jakarta. The sample numbered 60 respondents from 3 schools. The sample was obtained through a simple random sample, that is the researcher combined respondents in the population so that they would be measured in the same amount. This study has three variables divided into 2 independent variables (vocabulary mastery and reading interest variables) and 1 dependent variable (Understanding Narrative Text Skill variable). Data collection is done through multiple choice tests, questionnaires and written tests for all variables. Data acquisition was then analyzed using multiple correlation and regression techniques. Before performing a regression test, the test of analysis requirements must be achieved first, such as normality test and linearity test. The result of this research is 1) There is a significant influence of vocabulary mastery and reading interest together to the Ability to Understand Narrative Text of Junior High School Students in Kecamatan Makasar in East Jakarta. This is evidenced by the value of Sig. 0,000 <0.05 and F_ count = 29,769; 2) There is a significant influence of vocabulary mastery on the Ability to Understand Narrative Text of Junior High School Students in Kecamatan Makasar in East Jakarta. This is evidenced by the value of Sig. 0.000 <0.05 and thitung = 4.863; 3) There is a significant influence of reading interest on the Ability to Understand Narrative Text of Junior High School Students in Kecamatan Makasar in East Jakarta. This is evidenced by the value of Sig. 0.000 <0.05 and thitung = 4.438; . It shows that the ability to understand Narrative Text is highly controlled or influenced by their vocabulary mastery and reading interest. Keywords: Mastery of Vocabulary, Reading Interests, Ability to Understand Narrative Text